Evaluation of Azadirachta indica seed/spent Camellia sinensis bio-filler based jute fabrics–epoxy composites: Experimental and numerical studies. (April 2020) - Vijay, R; Vinod, A; Kathiravan, R; Siengchin, S; Singaravelu, D Lenin
The present work examined the thermo-mechanical characteristics of bio-fillers, namely Azadirachta indica seed powder, spent Camellia sinensis powder, their combinations filled jute fabrics–epoxy composites analytically and experimentally and compared it with the unfilled one. The test results showed that Azadirachta indica seed powder filled composites showed better mechanical properties with lesser voids, while spent Camellia sinensis powder and its composites showed better thermal stability. ANSYS analysis was used to show the stress distribution during the tensile and flexural testing. Scanning electron microscopy was used to study various characteristics of the fractured composites. A telephone stand was also fabricated to prove the application capability of best mechanical performer and analysed for deformation behaviour.